Blood Glucose Control and Daily Diabetes Management are Important for Patients - Lederman, Lynne (MD Conference Express, 2014)
If health care providers (HCPs) are aware of patients’ attitudes and needs, they can better assist patients in developing appropriate self-care plans. This article discusses results of an independent survey about what patients with diabetes or their caregivers learned or wanted to learn from their HCPs about diabetes.